Bhāṣāsāhitya caritraṃ - Pisharoṭi, Āttūr Kṛishṇa,Anitakumāri, Ṭ. (Tuñcattel̲uttaccan Malayāḷasarvakalāśāla, 2017)
History of Malayalam literature.
Keywords: Malayalam literature; History and criticism